2016
DOI: 10.1371/journal.pone.0157925
|View full text |Cite|
|
Sign up to set email alerts
|

Costs and Cost-Effectiveness of Hypertension Screening and Treatment in Adults with Hypertension in Rural Nigeria in the Context of a Health Insurance Program

Abstract: BackgroundHigh blood pressure is a leading risk factor for death and disability in sub-Saharan Africa (SSA). We evaluated the costs and cost-effectiveness of hypertension care provided within the Kwara State Health Insurance (KSHI) program in rural Nigeria.MethodsA Markov model was developed to assess the costs and cost-effectiveness of population-level hypertension screening and subsequent antihypertensive treatment for the population at-risk of cardiovascular disease (CVD) within the KSHI program. The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 61 publications
2
69
0
Order By: Relevance
“…A Markov model-based Costs and cost-effectiveness of hypertension screening and treatment in adults with hypertension in rural Nigeria showed that Screening and treatment for hypertension was potentially cost-effective with a wide range of uncertainty (24). This is in line with other studies that screening for adults below age 40 years is not-cost effective.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…A Markov model-based Costs and cost-effectiveness of hypertension screening and treatment in adults with hypertension in rural Nigeria showed that Screening and treatment for hypertension was potentially cost-effective with a wide range of uncertainty (24). This is in line with other studies that screening for adults below age 40 years is not-cost effective.…”
Section: Discussionsupporting
confidence: 80%
“…There is no enough evidence to recommend screening asymptomatic adults with no risk factor for hypertension. All studies form developed and developing countries revealed that screening adults aged 40 years with one or more risk factor is cost-effective (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). This is in line with WHO PEN package interventions for primary health care in developing countries (34).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Cost studies exist from several countries [4][5][6][7][8][9] around the world and in Africa for prevention [10] and for arterial hypertension [11].…”
Section: Introductionmentioning
confidence: 99%